Review of Spark Plasma Sintering Process. Issue 1 (December 2020) - Bubesh Kumar, D.; Selva babu, B; Aravind Jerrin, K M; Joseph, N; Jiss, Abdul
Abstract: This paper reviews the spark plasma sintering process. The spark plasma sintering (SPS) technique is a sintering technique in which the plasma is produced when the sintering is conducted. This plasma is used for the sintering of the powders. This paper deals with the various variables with effect the plasma sintering process. First the effect of pressure on SPS Process and its advantages. The review also highlights the research conducted by researchers on various materials and various sintering pressures. The effect of heat, the electro plastic effect was considered during the SPS Process review. The conventional sintering process is also considered in this review paper.